FUS and TDP-43 Phases in Health and Disease. Issue 7 (July 2021) - Portz, Bede; Lee, Bo Lim; Shorter, James
Abstract : The distinct prion-like domains (PrLDs) of FUS and TDP-43, modulate phase transitions that result in condensates with a range of material states. These assemblies are implicated in both health and disease. In this review, we examine how sequence, structure, post-translational modifications, and RNA can affect the self-assembly of these RNA-binding proteins (RBPs). We discuss how our emerging understanding of FUS and TDP-43 liquid–liquid phase separation (LLPS) and aggregation, could be leveraged to design new therapies for neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD), and limbic-predominant age-related TDP-43 encephalopathy (LATE). Highlights: Phase separation by proteins containing intrinsically-disordered regions (IDRs) underpins the biogenesis of functional membraneless organelles, as well as the formation of aggregated structures linked to neurodegenerative disease. One class of IDR, termed a prion-like domain (PrLD), is frequently found in RNA-binding proteins, such as FUS and TDP-43, which form condensates with a range of material states. FUS and TDP-43 form condensates in health and disease, and their phase separation is governed by distinct molecular grammar and regulation. Aberrant phase separation is likely more diverse than liquid-to-solid transitions and may include inappropriate liquid phases. Drugging condensates to treat disease is a promising strategy that may involve altering saturation concentrations of key scaffolds, or the specific partitioning of disruptive agents into discrete condensates.